Mercury speciation by CE: an update - Kubán, Petr; Pelcová, Pavlína; Margetínová, Jana; Kubán, Vlastimil (Electrophoresis, 2009)
This review provides an update on mercury speciation by CE. It includes a brief discussion on physicochemical properties, toxicity and transformation pathways of mercury species (i.e. methyl-, ethyl-, phenyl- and inorganic mercury) and outlines recent trends in Hg speciation by CE. CE is presented as a complementary technique to chromatographic separation techniques, especially in cases when speed, high efficiency and low sample volumes are required. The development of suitable sample preconcentration/isolation (sample stacking, ion exchange, liquid-liquid-liquid extraction, dual-cloud point extraction) to achieve low LODs for analysis of trace concentrations of mercury species in real samples is emphasized. Hyphenation of CE to element specific detectors (i.e. electrothermal atomic absorption spectrometry, atomic fluorescence spectrometry, inductively coupled plasma-optical emission spectrometry, inductively coupled plasma-mass spectrometry) is discussed as well as a potential of CE in interaction studies that may provide useful information on interaction of various Hg species with selected bio-macromolecules.
Keywords: sloučeniny rtuti; hmotnostní spektrometrie; Mass Spectrometry; Animals; lidé; organortuťnaté sloučeniny; zvířata; Sensitivity and Specificity; chemická frakcionace; Chemical Fractionation; Electrophoresis, Capillary; Organomercury Compounds; elektroforéza kapilární; senzitivita a specificita; Mercury Compounds; Humans